Aqidah al-Tauhid Baina al-Tasawwuf al-Sunni wa al-Tasawwuf al-Falsafi - Amal Fathullah Zarkasyi (Universitas Darussalam Gontor, 2010)
The philosophers and theologians for a long time, have been conducting a series of intense discourse on many issues from the perspective of tasawuf. Of course, in this regard, they use a theoretical basis and practical rationale. This article, describes the discourse above in the two different conversations perspective, between tasawuf Sunni and tasawuf falsafi. Tasawuf sunni group are represented by Al-Ghazali and al-Qushayri, confronted by Ibn Arabi and Ibn Sab’in from tasawuf falsafi group. Through a descriptive exploratory study, the researcher asserts that Al-Ghazali divides tauhid into four, tauhid of hypocrites, Muslims majority, muqarrabin, and siddiqin, all are based on ahl sunnah wa alJama’ah faith. While Al- ushayri, divides it into three; tauhid al-haq li al-haq, tauhid al-haq li al-khalq, and tauhid al-khalq li al-haq, all are based on empirical aspects of Irfani. In his study, the author concludes that tasawuf Sunni, focuses mainly on the issue of al-fana and wihdah al-syuhud in order to reach a peak of makrifah. Meanwhile, taswuf falsafi declares the existence of monoexistence, that is, human beings and God is one, similar to (wihdah al-wujud). Man is united with God expressed usually in the form syatahat. The implication is no taklif for humans.